Research on Ecological Affordances in L2 Classrooms Based on CNKI: Hotspots and Trends (2015–2025) - Jingru Chen; Chili Li (Translation and Linguistics (Transling), 2026)
This study addresses the need to systematically map the evolving research landscape of ecological affordances within China's foreign language teaching (FLT) context over the past decade (2015–2025). Employing a scoping review methodology, it analyzes relevant literature from the CNKI database using CiteSpace for visual knowledge mapping and cluster analysis. The research aims to identify publication trends, key research themes, influential contributors, and the developmental trajectory of this domain. 1) The findings reveal a field characterized by fluctuating but overall growth, delineated into three developmental phases; 2) Four primary research clusters were identified: Tracing studies on ecological affordances theory, transformational studies, practical studies, and expansions into emerging technological and cultural dimensions; 3) Key scholars and productive institutions, such as Dalian University of Foreign Languages and Shanghai International Studies University, were pinpointed; 4) The evolution of the field demonstrates a clear progression from theoretical importation to localized innovation and from macro-level constructs to nuanced, multi-perspective investigations. The study concludes that ecological affordances research has significantly enriched FLT discourse in China, offering a structured synthesis of its progress and suggesting pathways for further integrating ecological perspectives into pedagogical practice.